Refractory atrioventricular nodal re-entrant tachycardia: A rare manifestation of acute massive pulmonary embolism. Issue 1 (2015) - Patel, Jignesh; John, Jinu; Moskovits, Manfred; Yang, Felix; Hollander, Gerald; Shani, Jacob
No abstract available